2010
DOI: 10.1007/s10903-010-9391-z
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Tuberculosis Among Immigrants and Refugees at an Adult Education Center: A Community-Based Participatory Research Approach

Abstract: English as a Second Language programs serve large foreign-born populations in the US with elevated risks of tuberculosis (TB), yet little is known about TB perceptions in these settings. Using a community-based participatory research approach, we elicited perceptions about TB among immigrant and refugee learners and staff at a diverse adult education center. Community partners were trained in focus groups moderation. Ten focus groups were conducted with 83 learners and staff. Multi-level, team-based qualitativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
87
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(100 citation statements)
references
References 27 publications
8
87
0
2
Order By: Relevance
“…Of ten studies evaluating the views of individuals belonging to hard-to-reach populations on TB and TB services, seven were views of migrants, 15,29,31,34,35,37,38 one a mixed group of homeless people, migrants and drug users, 28 one of homeless people, 32 and one study reported on views of a Roma population. 36 No studies were found on views of prisoners, sex-workers and children living in hard-to-reach populations.…”
Section: Study Characteristics and Qualitymentioning
confidence: 99%
See 4 more Smart Citations
“…Of ten studies evaluating the views of individuals belonging to hard-to-reach populations on TB and TB services, seven were views of migrants, 15,29,31,34,35,37,38 one a mixed group of homeless people, migrants and drug users, 28 one of homeless people, 32 and one study reported on views of a Roma population. 36 No studies were found on views of prisoners, sex-workers and children living in hard-to-reach populations.…”
Section: Study Characteristics and Qualitymentioning
confidence: 99%
“…We included seven studies that reported views of hard-to-reach people regarding TB susceptibility, such as concepts of causes, risk factors, and modes of transmission. 15,28,29,31,34,36,38 Six studies focused exclusively on migrant populations, 15,29,31,34,36,38 and one on a mixed population of homeless people, drug users and migrants. 28 Smoking and 'other illnesses' were the most frequently mentioned perceived causes or risk factors for TB.…”
Section: Perceived Susceptibilitymentioning
confidence: 99%
See 3 more Smart Citations